Quality Analysis of Cloth Masks: Study of Material Types on Physical, Chemical, and Antibacterial Properties - Wahyuningsih, Sayekti; Ramelan, Ari Handono; Handayani, Selfi; Wiyono, Nanang; Rahardjo, Sentot Budi; Supriyanto, Agus; Lestari, Windy Ayu; Hartati, Retno; Hidayat, Rahmat (Indonesian Journal of Chemical Analysis (IJCA), 2023)
Utilizing personal protective equipment (PPE) is the important requirement for controlling and preventing of Covid-19 virus spread. The awareness of mask-wearing among the citizen and the development of fabric mask testing methods based on Indonesian Standards through the implementation of SNI 7648: Textile – Test of the air permeability on fabric; SNI 20743: The evaluating method of antibacterial properties using biological aerosol S. aureus and E. coli; SNI/ISO 4920: The surface wetness testing. This study shows that we need to understand and choose fabric masks correctlybesides being standardized. Fabric types influence the performance of the mask while protecting the user.